2019
DOI: 10.22159/ajpcr.2019.v12i7.33831
|View full text |Cite
|
Sign up to set email alerts
|

The ROLE OF HERBAL ANTIFUNGAL AGENTS FOR THE MANAGEMENT OF FUNGAL DISEASES: A SYSTEMATIC REVIEW

Abstract: Nowadays, fungal infection of skin is one of the most common dermatological problems worldwide. It has been investigated that 40 million people suffer from fungal infections. Superficial and subcutaneous fungal infections affect the skin, keratinous tissues, and mucous membranes. The dermatophytic infections, superficial candidiasis of the mouth, skin, or genital tract and infections due to Malassezia, such as pityriasis versicolor and Malassezia folliculitis are the main afflicting conditions. Systemic fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Development of resistance and relapse of disease are the major drawback of antifungal drugs. Therefore, there is a requirement to discover new antifungal therapies derived from plant sources having lesser side effects than conventional synthetic medicines [7]. In the current study, many Himalayan pteridophytes have been reported to have various bioactive molecules with appreciable antifungal activity [8,9].…”
Section: Introductionmentioning
confidence: 93%
“…Development of resistance and relapse of disease are the major drawback of antifungal drugs. Therefore, there is a requirement to discover new antifungal therapies derived from plant sources having lesser side effects than conventional synthetic medicines [7]. In the current study, many Himalayan pteridophytes have been reported to have various bioactive molecules with appreciable antifungal activity [8,9].…”
Section: Introductionmentioning
confidence: 93%
“…Fungi exist in two forms that are yeast and molds, former is typically a single, small and oval structure, whereas the latter consists of filamentous strands called hyphae. Fungi responsible for diseasecausing in healthy individuals are considered as a true pathogen, while those who develop the disease in immune-suppressed individuals are referred to as opportunistic pathogens, which mainly involve species of Mucor, Candida, Aspergillus, and Cryptococcus [2]. These four opportunistic fungal pathogens are reported to cause infections in covid-19 patients too [3].…”
Section: Introductionmentioning
confidence: 99%
“…parasiticus might be controlled by gene suppression. Screening of different medicinal potentials of herbals and natural products is one the enormous interest of scientists to discover new and novel lead compounds that they can solve new health problems such as fungi-toxigenic and so on all over the world [11]. This study is intended to screen two different plants from two families: E. connata and P. anisum.…”
Section: Introductionmentioning
confidence: 99%